PSYCHOLOGICAL PECULIARITIES OF CREATIVITY MANIFESTATION IN ACTIVITIES OF MANAGERS - A R Akimova; M I Volk (Peoples' Friendship University of Russia (RUDN University), 2016)
The modern economic, political and cultural situation in Russia calls for a new generation of managers, creative in their activities. In this regard we need to develop in them the personal qualities and characteristics which will enable them to achieve personal and professional success in various spheres of life. The article is devoted to studying features of ingenuity manifestation in managers as a systemic property of the personality. The features of creative activity, strategies for achieving goals, planning and time management in managers were analyzed in the article. The correlations of motivational, productive, dynamic and emotional sides of the personality traits of ingenuity, individual strategies of achieving goals and signs of time pressure in solving professional tasks for managers were considered. The practical recommendations developed in the study can significantly optimize the psychological support for managers, concerning the conditions of effective strategies for achieving goals, planning and time management, as the most important factors for their successful professional activity.